2003
DOI: 10.1177/154193120304701909
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Cognitive Elaboration Using Augmented Reality as a Training and Learning Paradigm

Abstract: Until now, little research attention in the area of Augmented Reality (AR) has been paid to the cognitive benefits engendered by this emerging technology. AR, the synthesis of computer images and text in the real world (Azuma, 1997), affords a supplement to normal information acquisition that has yet to be fully explored and exploited. AR achieves a more smooth and seamless interface by complementing human cognitive networks, and aiding information integration through multi-modal sensory elaboration, by utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 8 publications
1
7
0
1
Order By: Relevance
“…All students displayed increased memory retention compared with previous cohorts after one week. This is in line with the findings of Macchiarella and Vincenzi (2004) and Vincenzi et al (2003), who describe AR as impacting on long term memory by reducing the amount of information forgotten-in other words, simplifying the learning and reducing the amount learners need to remember. The researchers found that learners who used AR forgot less over time compared to those who did not use AR and that AR appeared to more effectively encode information into long term memory.…”
Section: Memory Retentionsupporting
confidence: 90%
See 1 more Smart Citation
“…All students displayed increased memory retention compared with previous cohorts after one week. This is in line with the findings of Macchiarella and Vincenzi (2004) and Vincenzi et al (2003), who describe AR as impacting on long term memory by reducing the amount of information forgotten-in other words, simplifying the learning and reducing the amount learners need to remember. The researchers found that learners who used AR forgot less over time compared to those who did not use AR and that AR appeared to more effectively encode information into long term memory.…”
Section: Memory Retentionsupporting
confidence: 90%
“…Radu ( 2014) comments that research indicates long term memory retention when using AR systems as superior to non-AR systems. In a study by Vincenzi et al (2003), students were shown to recall content learned with AR significantly better compared with students who did not use AR. Macchiarella and Vincenzi (2004) found that students learning about turbines using AR outperformed students who did not use AR when tested one week later.…”
Section: Memory Retentionmentioning
confidence: 98%
“…Regarding Memory, an enhanced memory encoding is stimulated by the physical immersion of MR experiences, and the fact that users interact with their senses, body, and limbs, which cause learners to encode sensing and proprioceptive information along with the educational content [28].…”
Section: Human Neuropsychological Empowerment In Learning Scenarios T...mentioning
confidence: 99%
“…Велики број студија указују на ентузијазам студената да се укључе у наставу и више задовољства при учењу (Dutta, 2015). Истраживања показују да је памћење садржаја више уз искуство путем појачане стварности него традиционалним путем: Винченци и сарадници (Vincenzi et al, 2003) и Валимонт и сарадници (Valimont et al, 2002) доказали су да се студенти који су учили о авионским турбинама уз асистенцију појачане стварности могу детаљније присетити садржаја у односу на студенте који су учили путем текста или видео-материјала.…”
Section: интернет ствари у високом образовањуunclassified